Observations of groundwater Quality Distribution in Tsunami affected areas using GIS (Case study in Weligama- Sri Lanka) - Piyadasa, Ranjana U. K. (My University, 2009)
Sri Lanka was hit its worst ever natural disaster and national tragedy on December 26, 2004, and shallow groundwater wells was completely damage. The study was conducted in Weligama coastal belt from May 2005 to May 2006 to identify scale of groundwater pollution due to tsunami. The network of ninety dug wells distributed over both the affected and non affected tsunami area was selected and location of the wells was detected with a GPS. Continuous monitoring of the water levels in the wells was conducted with respect to electrical conductivity (EC), total dissolved solids, salinity and pH. GIS package MAPINFOR was applied to plot the hydro-geological map and quality distribution maps. After one year and six months, EC values are still high and depend on the hydrogeological condition, elevation, topography and etc. The results of the study revealed that the electrical conductivity (EC) of groundwater quality situated in the Tsunami-affected region have EC values, on average, 1500- 3000 μ Siemens/cm.